E-CPR in Cardiogenic Shock Following Severe Mix-Intoxication with Beta-Blockers, Angiotensin-Converting Enzyme Inhibitors, Dihydropyridine Type Calcium Antagonist and Allopurinol – ECMO As A Bridge to Recovery - Mezger, Matthias; Gansewig, Aneke; Eitel, Ingo; Graf, Tobias (Archives of Clinical and Medical Case Reports, 2020)
Patient admission to intensive care unit (ICU) due to suggested intoxication either because of suicide or because of accident is not uncommon. We describe the case of a 49-year-old male patient who was admitted to our hospital after ingestion of approximately 75 tablets, consisting of beta-blockers, angiotensin-converting enzyme (ACE) inhibitors, dihydropyridine-type calcium antagonists and allopurinol. Only few hours after ingestion, the patient developed cardiac arrest in presence of preclinical healthcare professionals. Therefore, he was transferred to our heart-catheterization lab under mechanical supported chest compression and we commenced veno-arterial (VA) extracorporeal membrane oxygenation (ECMO) therapy. Heart function almost completely recovered, and finally, after explantation of VA- ECMO, he could be transferred to neurorehabilitation. <gdiv></gdiv>